Tari dan Pengendalian Diri - Daryono Daryono (Institut Seni Indonesia Surakarta, 2010)
Art is the same as knowledge, and both have a sense of clarity. One has a clarity of feeling, the other a clarity of thought. In the arts, there is a strong emphasis on the communication of feelings or emotions between the artists, the arrangement of artistic elements, and the ability to appreciate, understand, or bring to life a work of art. In the performing arts in particular, the beauty that is created is bound by time and space because of its â€˜transientâ€™ nature. The frame for creating the dynamics of such beauty is simply a deep understanding or appreciation of the art performance. In a dance performance, the dominant actor is the dancer himself. In this context, the dancer must be able to bring to life all the elements that are present at that time of the performance and to reflect upon them in such a way as is required. In this event, the understanding of beauty is contextual. For this purpose, the dancer must search to discover his own identity by travelling and exploring, bearing in mind that the elements of art such as feeling, understanding, perception, intuition, and so on are not given but must be discovered.Â Keywords: Dancer, self-control, intensity, and exploration.